Quadrinhos e cultura pop: uma pesquisa-ação em arte na escola - Costa, Maximiano Fernandes da (2025)
This study analyzes the teaching and learning relationships of pop culture elements and sequential art in a private school in João Pessoa-PB through actions linked to the teaching practice of the art teacher. The specific objectives are: 1) to present the teacher's aesthetic and cultural references related to pop culture and, based on this knowledge, to verify whether there is a possibility of their use as teaching tools aimed at teaching visual language; 2) to contextualize the references and previous experiences of a group of 15 (fifteen) students in the final years of elementary school; 3) to analyze the teaching and learning relationship developed during the action research activities. The methodology used was action research, coined by the authors Ivani Fazenda (2000) and Michel Thiollent (1986), focusing on Visual Culture Education and Comics, discussed with Fernando Hernández (2000), Luciana Borre (2010), Scott McCloud (2008) and Will Eisner (2010). The action research was developed based on the researcher's autobiographical experience as an art teacher and designer, as well as observations of the teaching material used in the school and the proposal of practical activities based on concepts extracted from composition techniques of sequential art and pop culture. It was concluded that: a) the teaching material used in the school presents a sophisticated vocabulary with technical terms that are not familiar to students at this educational stage, making the teaching-learning process difficult; b) it was evident that one of the main problems in the field of Art/Education, the difficulty in reading images, remains in contemporary educational practices;c) the experience of using comics and pop culture elements in art classes culturally connects different generations of people who can come together and discuss topics related to artistic knowledge; d) the experience of using comics and pop culture elements in art classes awakens curiosity and individual skills of perception, interpretation, appreciation, creation and critical sense; e) the way the art teacher interacts in the classroom is essential for the student to have access to the resources and content that are provided by the teaching materials, because the teacher has an important role as a mediator in establishing this teaching and learning process; f) pop culture serves as a link that generates this interaction between teacher and student in the teaching process, creating a closer bond and serving as a great tool to intensify this relationship that serves as a basis for educational experimentation focused on the art área; and g) no matter how much technology we have, it is human relationships that prevail in teaching and learning practices. We increasingly need to improve, strengthen, develop and strengthen ties between teachers and their students in order to expand this never-ending journey called education.